The molecular-level diagenetic clock of sinking marine organic matter - Heather J. Forrer; Michael R. Stukel; Amy M. McKenna; Huan Chen; Amy D. Holt; Sven A. Kranz; Robert G. M. Spencer (Proceedings of the National Academy of Sciences, 2025)
The marine biological carbon pump is driven by sinking particulate organic matter (POM). Sinking speed and remineralization rate determine flux attenuation in the mesopelagic. Since the fate of all marine organic matter is either complete remineralization or transformation to more stable products, diagenetic modifications impact carbon dioxide sequestration time from the atmosphere. To investigate particle transformation at the molecular level, we characterize the water-extractable organic matter (WEOM) fraction of sinking particles from dominant biogeochemical environments using ultrahigh-resolution mass spectrometry. We find distinct, inverse associations in molecular-level nitrogen content and degree of transformation (i.e., “stability”) of organic matter across a productivity gradient from coastal upwelling to oligotrophic conditions. Nitrogen enrichment and low stability were observed at the coastal upwelling site and persisted to depths >400 m. Further, carbon flux is strongly correlated with the relative abundance of stable WEOM (“Island of Stability” molecular formulae) across productivity regimes and depth. This suggests emergent patterns in epi- and mesopelagic diagenesis, highlighting that the molecular composition of sinking organic matter exiting the euphotic zone varies more across regions than as a function of depth. This is attributed to highly variable sinking rates and the microbial diagenetic histories within the euphotic zone. The stability–flux relationship is considered a “diagenetic clock” relative to organic matter formation where the relative abundance of Island of Stability molecular formulae describes the degree of departure from the organic matter molecular-level composition at formation. This ubiquitous trajectory of the diagenetic clock further underpins a global ocean molecular signature of sinking POM.